Terrorism threat in 2008 - Rohan Gunaratna (2009)
2008 will test the political will of the international community to fight insurgency and terrorism especially in Iraq, Tribal Pakistan and Afghanistan. With the impending withdrawal of US forces from Iraq and the growing instability in Pakistan following the assassination of Benazir Bhutto, the terrorist threat is likely to spread in 2008.